Strengthening Professional Attitudes of Undergraduate Makeup Education Students Through Self-Management and Makeup Skills Training - Sarah, Ririn Amaliah Putri; Ariastuti, Idun; Febianty , Syielvi Dwi; Surya, Wirma; Mandalika, Mandalika (Jurnal Pengabdian Masyarakat, Ilmu, dan Aksi, 2026)
Professional readiness in beauty and makeup education requires the integration of technical competence and professional attitudes. This community service program strengthened professional attitudes of undergraduate Makeup Education students through integrated self management and professional makeup skills training. Using a qualitative participatory design, the program combined training sessions and hands on workshops with 80 students at Institut Seni Indonesia Padangpanjang. Data were collected through participant observation, guided reflection, short interviews, and documentation, and analyzed thematically using rubrics and indicators. Baseline observations showed only 52.5% arrived on time, 46.3% prepared complete tools, 58.8% displayed low confidence, and about 60% lacked understanding of grooming standards. After the program, 87.5% attended on time, 72.5% participated in discussions, and 65% volunteered for demonstrations. Rubric ratings improved from 45% to 82.5% for discipline and work readiness, from 41.3% to 78.8% for professional communication, and from 37.5% to 85% for professional appearance and hygiene. Reflections indicated 81.3% improved understanding of self management and ethics, and 76.3% reported higher confidence in practice. Overall, the model supports holistic professionalism.